Exploring the Impact of Role-play Strategy on Enhancing EFL Students’ Speaking Skills: Teachers’ and Students’ Perspectives at Misurata University - Hmaid, Yaseen; Elmurabit, Aisha ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2025)
The current study investigates the perceptions of Libyan university students and teachers regarding the role-play strategy as a pedagogical tool for enhancing English as a Foreign Language (EFL) speaking skills. Adopting a mixed-methods approach, the study employed a questionnaire and semi-structured interviews as instruments for data collection. Forty first-semester EFL students from the Faculty of Arts at Misurata University completed the questionnaire, while ten EFL instructors participated in interviews to provide qualitative insights into the effectiveness and challenges of implementing role-play in speaking classes. Quantitative data were analyzed using descriptive statistics, whereas qualitative data were examined through content analysis. The findings reveal that both students and teachers hold positive attitudes toward the use of role-play in developing speaking proficiency. Students reported that the technique increased their confidence, enriched their vocabulary, improved their pronunciation, and enhanced their engagement and enjoyment in learning English. Similarly, teachers acknowledged the effectiveness of role-play in improving students’ communicative competence and promoting interactive learning environments. The study concludes that role-play constitutes an effective instructional strategy for fostering oral communication skills among EFL learners in the Libyan university context. Implications for pedagogy and recommendations for future research are also discussed.